FAKTOR PENDUKUNG PENCAPAIAN KEMAMPUAN GURU SD DALAM MENGGUNAKAN APLIKASI ANATES MELALUI PELATIHAN - Sudarto, Sudarto; Firdaus, Firdaus; Rukayah, Rukayah (Bajang Institute, 2024)
The Community Partnership Program (CPP partners are the elementary school teachers in Bone Regency who are partners of UNM through an MOU. Objective: to explain the supporting factors for the teachers’ success in training on the use of the Anates application. Data collection techniques include: observation, questionnaires, and interviews. Results and Conclusions: the supporting factors for the success of implementing training in using the Anates application to analyze test items are: participant enthusiasm, encouragement from the principal, a comfortable training atmosphere, the methods taught/demonstrated by the trainer are easy to apply, there is a mutual assistance between the training participants, and the trainer directly provides guidance/guidance to participants who need it